Beijing +30: a global and Zambian review of women’s political participation and their impact on development outcomes - Ndhlovu, Patricia Mwaka Mphanza (Frontiers in Political Science, 2025)
This study examines global and Zambian progress on women’s parliamentary participation from 1995 to 2025, in line with Section G of the Beijing Declaration and Platform for Action. It highlights the developmental significance of inclusive political representation and the persistent underrepresentation of women, averaging below 30% globally and in Zambia. The study employs a qualitative desk review methodology, systematically analysing academic literature, United Nations documents, and national policies and reports to synthesise existing knowledge and trends. Descriptive statistics are used to illustrate participation patterns over the past three decades, whilst qualitative analysis explores structural and societal barriers that continue to constrain women’s full engagement in political life. Despite notable policy reforms and gender responsive measures, progress remains slow. Evidence shows that when women are meaningfully represented, policies better reflect diverse needs and foster inclusive development. To accelerate change, the study recommends targeted measures including gender quotas, gender-responsive electoral systems, legal reforms, and institutional support mechanisms such as mentorship, training, and financial access to strengthen women’s political agency.